The end of a mystery: transferring Streptostachys robusta to Ichnanthus (Poaceae, Paspaleae) based on DNA sequences, morphology and leaf anatomy - Oliveira, Reyjane Patricia De; Jesus-Junior, Luiz Antonio De; Mota, Aline Costa Da; Silva, Christian Da (Phytotaxa, 2017)
Streptostachys robusta was described from a single collection from Southern Bahia, Brazil. Because of the early flowering stage of the type material, with immature spikelets, the taxonomic position of this species remained uncertain for more than three decades. We obtained new collections of the taxon, and using several lines of evidence demonstrate that S. robusta belongs to the genus Ichnanthus and is related to I. bambusiflorus. We transfer this species to Ichnanthus, as I. robustus, and amend its description to reflect a broader range of morphological variation, based on study of all known specimens. Details of fully developed spikelets are presented for the first time. We also propose an epitype for the name S. robusta because the holotype and isotypes do not allow precise application of the name.